Public sector management : theory, critique and practice (London, 1994)
"Drawing together key contributions to the field, this innovative Reader provides a broad-ranging overview of both the theory and practice of public service management. The book: outlines the social, political and economic contexts in which management has emerged as a crucial issue in the public sector of modern democratic countries; introduces the major theories, issues and concepts involved in defining and understanding public sector management; analyzes some of the key values underpinning the idea of the public domain; and examines some of the main challenges in terms of particular strategies, techniques and competences which have been proposed to improve management for public services."